UJI POTENSI EKSTRAK DAUN EKALIPTUS (Eucalyptus sp.) SEBAGAI INSEKTISIDA NABATI TERHADAP HAMA KUTU PUTIH (Paracoccus marginatus) PADA PEMBIBITAN AKASIA MANGIUM (Acacia mangium) - Dian Andi Syahputra; M. Mardhiansyah; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Acacia mangium is one of the plant that was planted in industrial timber plantations as the main material of paper. This plant no need the specific area to grow and can produce the best wood. Acacia mangium nursery have a problem to the pest. One of the pest that often attack the young plants in the nursery is Paracoccus marginatus. It can makes the low number of productivity. The efforts to control this pest is generally controlled by using chemical pesticides. One of the alternative that can be used to minimaze the application of chemical pesticide was using of Eucalyptus sp. leaf extract. This research aimed to know the influence of applicaton Eucalyptus sp. leaf extract to the attacking activity Paracoccus marginatus to the Acacia mangium nursery. The research was conducted at the Laboratory of Plant Pest, Agriculture Faculty of Riau University in March to April 2016. This research uses a Completely Randomized Design Method, which consists 4 treatments and 4 replicates with concentration levels of botanical pesticide. P0 = concentration Eucalyptus sp. leaf extract 0 g/l of water; P1 = 10 g/l of water; P2 = 20 g/l of water; P3 = 30 g/l of water. The results showed that the application of Eucalyptus sp. leaf extract at the concentration of 30 g/l water is the best concentration in controlling Paracoccus marginatus with results initial time of death fastest is 18.25 hours, the fastest time of turning off 50% (LT50) is 56.50 hours and total mortality amounted to 90.00%. Keywords: Acacia mangium, Paracoccus marginatus, Eucalyptus sp., botanical insectiside